Perfil de saúde de sujeitos residentes em instituições terapêuticas - Manfredi, Paula (2019)
The aging process is evidenced by the current demographic transition, in which it is marked by the reduction of fertility and birth rates and an increase in the proportion of the elderly and the life expectancy. Population aging brings with it the need for recovery and health promotion for all individuals, but some population groups require more attention as individuals with mental disorders, especially those who are institutionalized, since in most cases they have an increase of health compromise. This population, because it has more changes in quality and life expectancy, require a greater accompaniment and planning. Therefore, the objective of this study is to identify the health profile of subjects residing in therapeutic institutions, focusing on the prevalence of polypharmacy and evaluation of nutritional status. This is a cross-sectional study with individuals with mental disorders in Private Therapeutic Homes (PTH) with a total sample of 254 medical records. In the scientific production I, the objective was to verify the prevalence of polypharmacy and associated factors in subjects with mental disorders hospitalized in therapeutic residences in the city of Passo Fundo. The outcome, polypharmacy, was evaluated considering the use of at least 5 medication of continuous use. We investigated 254 subjects in housing in therapeutic institutions, the prevalence of polypharmacy was 55.6%. In the bivariate analysis it was possible to verify a lower prevalence of polypharmacy among subjects who did not present clinical disease and with a shorter hospital stay (p <0.05). The same result was maintained in the multivariate analysis, with a prevalence ratio of 0.670 for clinical disease and 0.661 for hospitalization time. In cinetificative production II, the objective was to describe the nutritional status of subjects residing in a therapeutic institution. The sample size was 160 individuals, since not all authorized the anthropometric measurements. It was identified that 66.2% of the sample was overweight, according to BMI. From waist circumference, prevalence of 71.2% of high or very high risk for the development of cardiovascular diseases in both sexes was observed. There was an association between high and very high waist circumference, female gender and presence of clinical disease (p <0.05). The study identified a high prevalence of polypharmacy associated with hospitalization time and presence of clinical disease, and the association between high and very high waist circumference, female sex and presence of clinical disease. These results deserve attention, since they are young subjects and at risk of early mortality due to the clinical condition itself. It is suggested that federal, state and municipal health managers evaluate the conditions of free psychosocial care in their territories, in order to better the quality of life and health of these subjects.